Perancangan Model Ontologi untuk Sistem Pencarian Sepeda Motor Bekas - I Kadek Dwi Adnyana; I Putu Gede Hendra Suputra (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2024)
Motorcycles are a means of transportation that people often use to meet their daily needs. However, not everyone can afford to buy a new motorbike, so many people are switching to used motorbikes. Finding a used motorcycle that suits your needs can be a difficult challenge for some people and of course there are many factors that must be considered. The solution that can be done for this problem is to use the semantic ontology model with the Methodology method. The design of the ontology model of used motorcycle products uses the protégé application, the ontology model is developed into a structure in protégé with a hierarchical structure of classes, slots, properties, etc. Used motorcycle product ontology development model produces 13 classes, 5 object properties, 5 data properties, and 68 individuals or instances in each class. The ontology evaluation process by performing SPARQL queries is used to get the appropriate results.